PEMANFAATAN TEKNOLOGI INFORMASI DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI LINGKUNGAN PEMERINTAH KOTA BANDUNG - Ridwan Fathony; Muradi Muradi; Novi Indrawati Sagita (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2021)
During the covid-19 pandemic, state organizers were forced to innovate public services thatcontinued to put forward health protocols. Public services provided by the state apparatus inthis case (ASN) must run well and be easily understood and presented by the public. Thisresearch aims to find out the extent to which the utilization of information and conditions ofhuman resources and technology used from each service provider to the community andbeneficiaries (community). By taking primary data from observations and interviews ofinformants directly, as well as the utilization of digital data this research method is carried outby developing data analysis krtitis to the phenomenon of information technology. the resultsshowed that the utilization of technology has not been fully used properly with severalinhibitory factors from internal and external state organizers (service providers) withbeneficiaries (communities).